Rhizobium Bacteria’s activity in the root - S.B. Mustanov; X. Berdimurodov; L.Sh.Toshtemirov (Proceedings of The ICECRS, 2019)
This article examines the activity of pea root bacteria and their effect on the agrochemical composition of the soil, which shows the effects on the activity, weight and soil fertility in the phases of germination, flowering, and legume cultivation.